GE_GERICHTE A/2401/2023 vom 27. Juni 2024 - GE Cour de justice (2024)
Cst..8.al1; LPC.9a.al1; LPC.11.al1.letc; LPC.11a.al2; LPC.11a.al3; LPC.12.al1; LPC.12.al4; aLPC.11.al1.letc; LPCC.1A.al1.leta; LPCC.4; LPCC.5